PENGARUH ADVERTISING DENGAN KONSEP AIDA TERHADAP KEPUTUSAN PEMBELIAN KARTU PERDANA MERK simPATI - Khomariyah, Siti; Andayani, Sri; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2015)
Costumerâ€™s decision to buy the cellular card is influenced by the concept of AIDA while used to promote the advertisement, become the problems of company. Therefore, in this study, the writer chooses the title â€œPengaruh Advertising Dengan Konsep AIDA Terhadap Keputusan Pembelian Kartu Perdana Merk simPATI (Studi Eksplanasi Pengaruh Advertising Dengan Konsep AIDA Terhadap Keputusan Pembelian Kartu Perdana Merk simPATI di Universitas 17 Agustus 1945 Surabaya â€.Â  This research conducted at University of 17 Agustus 1945 Surabaya. However, the study is aimed for knowing the influence of each free variable, such as attention, interest, desire and action to the costumerâ€™s decision for buying SimPATI cellular card, and also for knowing the influence of variable which most dominant based on AIDA concept toward the costumerâ€™s decision for buying SimPATI cellular card. As the result of this study, each free variable, such as: attention, interest, desire and action influence the purchasing order and action variable has the dominant influence to determine the purchasing.Â Â Â  Â Keywords: Attention, Interest, Desire, Action, Purchasing decision.